Turning Waste into Profit: Plastic Waste Recycling Workshop into Crafts for Cipta Wacana Students at Bank Sampah Malang - Priyanti, Novie Ary; Lisdianita, Arinda Eka; Habiburrahman, Novan; Retno Palupi; M. Zainul Muttaqin; Agung Hariadi (⁠International Journal of Asia Pacific Community Service, 2025)
Plastic waste is one of Indonesia’s most critical environmental challenges, comprising approximately 17% of the nation's 64 million tons of annual waste. This study explores the impact of a recycling workshop that transformed plastic waste into handicrafts, conducted at the Malang Waste Bank and involving students from Universitas Kristen Cipta Wacana Malang. Using an activity-based participatory approach, the workshop aimed to enhance students’ environmental awareness, practical recycling skills, and understanding of circular economy principles. Data were collected through observations, interviews, questionnaires, and documentation. The results showed a significant increase in students’ knowledge of the 3R concept (Reduce, Reuse, Recycle), along with improved technical skills in sorting, melting, and crafting recycled products such as bags, hats, and wallets. The workshop also encouraged environmental entrepreneurship by demonstrating that waste can be transformed into valuable and marketable items. This initiative exemplifies how community-based, hands-on learning experiences can foster sustainability values in higher education and support the Merdeka Belajar Kampus Merdeka (MBKM) policy framework.